Contribution of a Real Depth Distance Stereoacuity Test to Clinical Management. (5th July 2009) - Young, B. J.; Sueke, H.; Wylie, J. M.; Kaye, S. B.
Abstract : Measurement of Stereopsis forms an important part of the clinical assessment of patients with disorders of ocular motility. The introduction of a real depth distance stereoacuity test (FD2) was evaluated in clinical practice and to what extent the introduction affected clinical management. Seventy-three patients under evaluation before and following the introduction of the test were included. Combined thresholds were measured at near using the Frisby and TNO test and at distance using the FD2. Fifty healthy controls were included. Forty-five patients demonstrated Stereopsis using the FD2 and 23 of these had a change in their management based in part on their responses using the FD2. Patients with evidence of Stereopsis using the FD2 were significantly more likely to have change in their management than expected from the whole sample (P = .02 ). The introduction of a real depth distance stereoacuity test into clinical practice contributed to a change in management when used in conjunction with other tests. The usefulness of the FD2 is limited by its range at 6 m. Use at closer distances necessitates the calculation of binocular threshold from the combined and monocular threshold.